High cyclability of carbon-coated TiO2 nanoparticles as anode for sodium-ion batteries. (1st March 2015) - Ge, Yeqian; Jiang, Han; Zhu, Jiadeng; Lu, Yao; Chen, Chen; Hu, Yi; Qiu, Yiping; Zhang, Xiangwu
Highlights: Titanium oxide nanopaticles were modified by carbon coating from pyrolyzing of PVP. Carbon coating gave rise to excellent cycling ability of TiO2 for sodium-ion batteries. The reversible capacity of carbon-coated TiO2 reached 242.3 mAh g −1 at 30 mA g −1 . Good rate performance of carbon-coated TiO2 was presented up to 800 mA g −1 . Abstract: Owing to the merits of good chemical stability, elemental abundance and nontoxicity, titanium dioxide (TiO2 ) has drawn increasing attraction for use as anode material in sodium-ion batteries. Nanostructured TiO2 was able to achieve high energy density. However, nanosized TiO2 is typically electrochemical instable, which leads to poor cycling performance. In order to improve the cycling stability, carbon from thermolysis of poly(vinyl pyrrolidone) was coated onto TiO2 nanoparticles. Electronic conductivity and electrochemical stability were enhanced by coating carbon onto TiO2 nanoparticles. The resultant carbon-coated TiO2 nanoparticles exhibited high reversible capacity (242.3 mAh g −1 ), high coulombic efficiency (97.8%), and good capacity retention (87.0%) at 30 mA g −1 over 100 cycles. By comparison, untreated TiO2 nanoparticles showed comparable reversible capacity (237.3 mAh g −1 ) and coulombic efficiency (96.2%), but poor capacity retention (53.2%) under the same condition. The rate performance of carbon-coated TiO2 nanoparticles was also displayed as high as 127.6 mAh g −1 at a current density of 800 mA g −1 . The improved cycling performance and rate capability were mostly attributed to protective carbon layer helping stablize solid electrolyte interface formation of TiO2 nanoparticles and improving the electronic conductivity. Therefore, it is demonstrated that carbon-coated TiO2 nanoparticles are promising anode candidate for sodium-ion batteries.